Upaya Meningkatkan Disiplin Guru Dalam Kehadiran Mengajar Dikelas Melalui Penerapan Reward and Punishment Guru SD Negeri Cibalagung 2 Kota Bogor - Nurhidayah, N. (Universitas Pakuan, 2023)
Efforts to Improve Teacher Discipline in Teaching Attendance in Class Through the Implementation of Reward and Punishment for Elementary School Teachers (SD Negeri Cibalagung 2 Kota Bogor)Improving the quality of learning in schools really depends on several factors. A very important factor, among others, is the implementation of school culture towards improving quality. School culture is a positive thing that must be maintained and implemented by all school members without feeling forced. One of the school cultures that must be maintained is the issue of discipline, including teacher discipline in attending class during the teaching and learning process. To improve teacher discipline, efforts can be made in various ways. In this School Action Research, action was tried in the form of implementing Reward and Punishment for teachers at SDN Cibalagung 2, West Bogor District, Bogor City. This research was carried out in two cycles, because from the results of the research and data analysis, it turned out that in the second cycle, teacher discipline in class attendance during the teaching and learning process increased and met the indicators that had been set at 75%. From the results of this research, it can be concluded that improving teacher discipline in class attendance during teaching and learning activities can be done by implementing Reward and Punishment for teachers.